БАЗОВОЕ ИСПОЛНЕНИЕ РЕГУЛЯТОРА АВИАДВИГАТЕЛЯ И ЕГО МОДИФИКАЦИИ - Ранченко, Геннадий Степанович; Буряченко, Анна Григорьевна; Грудинкин, Вячеслав Михайлович; Данилов, Всеволод Владимирович (Avìacìjno-kosmìčna tehnìka ì tehnologìâ, 2020)
It is shown that the creation of a unified electronic control and control equipment for aircraft gas turbine engines is one of the determining trends in the experimental design work of enterprises developing components of aircraft equipment. The results of the creation of some helicopter and aircraft engine controllers (turboshaft and turboprops) in JSC Element are presented. The basic model for them was the regulator RDC-450М (category A component product according to AP-21 classification), which was developed for the AI-450M family of turboshaft engines of Мi-2M and Mi-2MSB and in 2014 received the APPLIANCE DESIGN APPROVAL. There is given information concerning the mass-produced regulator RDTs-450M rework to meet the new requirements specified by the engine designer as the results of certification tests of the AI-450M engine and state tests of the Mi-2M and Mi-2MSB helicopters. It is shown that the rework was carried out taking into account the maximum possible “modifiability” of the regulator, which is the maximum ease of its adaptation in the future to new requirements, including requirements for working with other types of engines, including turboprops. The modular principle of constructing the functional structure and design of the regulator is described; its structural scheme is given. Data are given on the results of equivalent cyclic tests of the regulator RDTs-450M, which was modified to meet the new requirements, and on subsequent work on its adaptation to monitor and regulate the modes of turboprop aircraft engines AI-450C (including its modifications) and MS-500V-02S. Information is given on the newly developed regulators RDTs-450M-S, RDTs-450M-S-1, RDTs-450M-S-T-P, RDTs-450S-500, among which there is an engine regulator designed for an unmanned aerial vehicle. It is noted that the modular design assumes the presence of a significant number of board-to-board connections, and the prospects of increasing the reliability of regulator having a modular design by using the technology of flexible-rigid boards are described.